Review of âThe Chinese Belt and Road Initiativeâ: Indonesia-China Cooperation and Future Opportunities for Indonesiaâs Port Cities Development - Hermaputi, Roosmayri Lovina; Jiajia, Gong; Chen, Hua (The ITB Journal Publisher, 2017)
Abstract. This paper aims to elaborate the Chinese Belt and Road Initiative, through a SWOT analysis of the China-Indonesia relation and investment conditions and a descriptive analysis of the impact of the development of Indonesian port cities. The Belt and Road Initiative emerges as a new Chinese government strategy of cooperation with neighboring countries. It will revitalize the existing Silk Road and build a Maritime Silk Road, connecting South East Asia through the Indian Ocean to the Middle East and North Africa. It exhibits similarities with Indonesiaâs Maritime Toll program. Indonesiaâs involvement in the Maritime Silk Road offers many opportunities to foreign countries to invest and participate in their economic development. However, Indonesiaâs Investment Coordinating Board states that Chinese investment realization in Indonesia was no more than 10% in 2014. The output of this paper consists of recommendations for both parties to create a conducive investment climate by getting to know each country well, assuring the realization of planned investment, taking advantage of the China-ASEAN Free Trade Zone and the AIIB, and upgrading the investment system.Keywords: The Belt and Road Initiative, Indonesia-China Relation, Foreign Direct Investment, Indonesiaâs Port City Development.Abstrak. Makalah ini bertujuan untuk menguraikan Inisiatif Satu Sabuk dan Satu Jalan (China Belt and Road Initiative (OBOR), dengan menggunakan analisis SWOTÂ mengenai kondisi hubungan dan investasi China-Indonesia dan analisis deskriptif mengenai dampak pembangunan kota-kota pelabuhan di Indonesia. Inisiatif Satu Sabuk dan Satu JalanÂ muncul sebagai strategi baru pemerintah Tiongkok untuk bekerjasama dengan negara-negara tetangga. Inisiatif ini akan merevitalisasi Jalan Sutra dan membangun Jalur Sutra Maritim yang menghubungkan Asia Tenggara melalui Samudra Hindia dengan Timur Tengah dan Afrika Utara. Hal ini menunjukkan kesamaan dengan program Tol Maritim di Indonesia. Keterlibatan Indonesia di Jalur Sutra Maritim menawarkan banyak kesempatan kepada negara-negara asing untuk berinvestasi dan berpartisipasi dalam pembangunan ekonomi di Indonesia. Namun, Badan Koordinasi Penanaman Modal menyatakan bahwa realisasi investasi Tiongkok di Indonesia tidak lebih dari 10% pada tahun 2014. Hasil makalah ini terdiri dari rekomendasi bagi kedua belah pihak untuk menciptakan iklim investasi yang kondusif dengan mengenal kondisi masing-masing negara dengan baik, memastikan realisasi investasi yang telah direncanakan, mengambil keuntungan dari Kawasan Perdagangan Bebas ASEAN-Tiongkok dan AIIB, dan meningkatkan sistem investasi.Kata kunci: Inisiatif Satu Sabuk dan Satu Jalan, Hubungan Indonesia-Tiongkok, Investasi Asing Langsung, Pembangunan Kota Pelabuhan di Indonesia